2023
DOI: 10.24875/gmm.m20000336
|View full text |Cite
|
Sign up to set email alerts
|

Morphea: a practical review of its diagnosis, classification and treatment

Abstract: Morphea, or localized scleroderma, is a rare disease of the connective tissue that manifests itself with localized sclerosis of the skin and, in some cases, with extracutaneous manifestations. Its etiology is not fully understood, but it is believed that there is genetic predisposition, in addition to environmental triggering factors. Classification of the disease is not simple due to its multiple presentations; however, it is useful in order to define the treatment, which should be individualized and started … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…6 Decreased antioxidant capacity such as lower levels of serum alpha-tocopherol, selenium, carotene and ascorbic acid, and higher values of oxidant molecules contribute to the oxidative stress mechanism in scleroderma pathogenesis. 3 In in-vitro studies it has been shown that fibroblasts cultured from scleroderma lesions, release increased amounts of reactive oxidizing species which on the other hand induce proliferation and activation of fibroblasts. This leads to increase in type I collagen synthesis, overproduction of proinflammatory and pro-fibrotic cytokines, and worsens vascular Glutathione S transferases are a large superfamily that metabolize the detoxification of reactive-oxygen species of S-thiolated proteins that damage cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6 Decreased antioxidant capacity such as lower levels of serum alpha-tocopherol, selenium, carotene and ascorbic acid, and higher values of oxidant molecules contribute to the oxidative stress mechanism in scleroderma pathogenesis. 3 In in-vitro studies it has been shown that fibroblasts cultured from scleroderma lesions, release increased amounts of reactive oxidizing species which on the other hand induce proliferation and activation of fibroblasts. This leads to increase in type I collagen synthesis, overproduction of proinflammatory and pro-fibrotic cytokines, and worsens vascular Glutathione S transferases are a large superfamily that metabolize the detoxification of reactive-oxygen species of S-thiolated proteins that damage cells.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased antioxidant capacity such as lower levels of serum alpha‐tocopherol, selenium, carotene and ascorbic acid, and higher values of oxidant molecules contribute to the oxidative stress mechanism in scleroderma pathogenesis 3 . In in‐vitro studies it has been shown that fibroblasts cultured from scleroderma lesions, release increased amounts of reactive oxidizing species which on the other hand induce proliferation and activation of fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations